Tokopedia and Shopee Marketplace Performance Analysis Using Metrix Google Light-house - Suhaili Sahibul Muna; Nurdin Nurdin; Taufiq Taufiq (International Journal of Engineering, Science and Information Technology, 2022)
The development of the marketplace is growing very rapidly and has become familiar in the lives of Indonesian people. The term marketplace has also been imprinted in the general public as a place for buying and selling online without having to meet physically. In practice, the marketplace has also provided a lot of convenience and comfort in shopping, starting from transaction security and selection of varied shopping items, also equipped with estimates in shipping. It doesn't stop there; the development of the marketplace has also penetrated almost all products, including services, food, music, books, household products, airline tickets, and even investments that can be made in the marketplace. Google Lighthouse is a complex metric where the assessment includes in terms of Performance, Accessibility, Best Practices, and SEO, which is presented with a score of 0 to 100 in other words, Google will assess a website with a predetermined metric and then audit it to improve accessibility and SEO. a website. The results of this study are expected to be able to present actual analytical information based on the matrix determined by Google Lighthouse for future improvements where the Tokopedia marketplace gets a performance value with a yellow score of 85, which can be optimized by minimizing the speed index 3.7s, time to interactive 5.9s and total blocking time is 390s to be more optimal in terms of performance and Shopee has decreased in performance with a value of 13 red on first contently paint 2.8s, speed index 16.8s, time to interactive 26.5s, largest contently paint 16.3s, cumulative layout shift 0.484 and total blocking time of 1,710ms to be further assessed for optimal results. Based on this test, it can be concluded that Tokopedia is superior to Shopee from various aspects of the matrix tested.